2023
DOI: 10.22434/ifamr2021.0130
|View full text |Cite
|
Sign up to set email alerts
|

Social embeddedness and agricultural technology diffusion from the perspective of scale differentiation – a case study from China

Abstract: Social embeddedness always plays important role in facilitating agricultural technology diffusion. However, in China, dramatic changes have occurred in the social embeddedness of rural households in the transition from ‘acquaintance society’ to ‘semi-acquaintance society’. Could this be the reason for the debate over the role of social embeddedness? What are the differences in the role of social embeddedness between farmers with different land scales? Based on survey data from 583 rural households from Zhejian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The Chinese culture is deeply rooted in the Confucian ethical and philosophical system, which is characterised by a highly collectivistic culture (social relations and embeddedness; Li and Li, 2022;Chen, 2011), a strong hierarchy (Meyer, 2021), and e.g., the concept of 'learning from the master' (Hoste et al, 2012), resulting in a typical copying behaviour, as copying a demonstrated success is a safe way to adapt. Face (loss) (e.g., Hu, 1944;Ho, 1976), a sociological concept of reputation, plays a significant role in Chinese culture.…”
Section: 1mentioning
confidence: 99%
“…The Chinese culture is deeply rooted in the Confucian ethical and philosophical system, which is characterised by a highly collectivistic culture (social relations and embeddedness; Li and Li, 2022;Chen, 2011), a strong hierarchy (Meyer, 2021), and e.g., the concept of 'learning from the master' (Hoste et al, 2012), resulting in a typical copying behaviour, as copying a demonstrated success is a safe way to adapt. Face (loss) (e.g., Hu, 1944;Ho, 1976), a sociological concept of reputation, plays a significant role in Chinese culture.…”
Section: 1mentioning
confidence: 99%